The night before Christmas poem - Moore, Clement Clarke; Brett, Jan 1949- (New York : Scholastic, 1999)
Presents the well-known poem about an important Christmas visitor.
"This edition is only available for distribution through the school market"--[P. 4] of cover.
79101
Keywords: Santa Claus -- Juvenile poetry; Christmas -- Juvenile poetry; Children's poetry, American